Hubungan Sedentary Lifestyle dengan Status Gizi Remaja pada Masa Pandemi Covid-19 di SMPN 14 Jember - Nabila Alfionita; Lantin Sulistyorini; Eka Afdi Septiyono (Pustaka Kesehatan, 2023)
More nutritional status occurs because of an imbalance between energy intake and energy expenditure. High energy intake is the result of excessive food consumption, while low energy expenditure is the result of a lack of physical activity. The sedentary lifestyle has increased during the Covid-19 Pandemic. Sedentary lifestyle triggers the risk of overweight and obesity in adolescents. This research uses an analytic observational design with a cross-sectional approach which aims to determine the relationship between sedentary lifestyle and nutritional status of adolescents. Respondents in this study were adolescents aged 13-15 years. The number of samples was 70 respondents used purposive sampling technique. The instrument used was the Adolescent Sedentary Activity Questionnaire (ASAQ) and measurement of nutritional status using standard anthropometric z-score tables to assess nutritional status in children aged 5-18 years. This study obtained the results of the Spearman rank test, obtained a p-value of 0.000 (<0.05) and a correlation coefficient of 0.470, which means that there is a significant and unidirectional relationship with moderate strength between the sedentary lifestyle and the nutritional status of adolescents. It can be concluded that with increasing sedentary lifestyle, nutritional status will also increase. Sedentary lifestyle is a factor associated with overweight status because low physical activity causes fat accumulation due to not burning calories.